Breadfruit Peel Derived Pectin as a Natural Polymer for Gastroretentive Floating Beads of Amoxicillin: Formulation and Characterization - Puteri, Cut Intan Annisa; Fauzi, Ziza Putri Aisyia; Rahmadani, Rahmadani; Sari, Febia; Hartini, Putri Tri (Sciences of Pharmacy, 2026)
Amoxicillin is widely used to treat gastric infections; however, conventional oral dosage forms often exhibit rapid gastric emptying and short gastric residence time, which may reduce therapeutic effectiveness. Gastroretentive floating drug delivery systems can prolong gastric retention and provide sustained drug release. This study aimed to develop gastroretentive floating beads of amoxicillin using pectin extracted from breadfruit peel (Artocarpus altilis) and compare their characteristics with those prepared using commercial pectin. Floating beads were prepared by ionotropic gelation using calcium chloride as a crosslinking agent and sodium bicarbonate as a gas-forming agent. The beads were characterized for morphology, floating behavior, entrapment efficiency, and drug release. All evaluations were performed in triplicate (n = 3). The prepared beads exhibited spherical morphology with diameters of 0.24–0.42 mm and weights of 9.26–11.38 mg. Floating lag time ranged from 10–22 seconds, and all formulations remained buoyant for up to 8 hours. Entrapment efficiency ranged from 31–47%, with formulations prepared using commercial pectin showing values of 34–47% and breadfruit peel-derived pectin showing values of 31–43%, with formulation F3 containing 3.5% commercial pectin showing the highest value. In vitro drug release studies demonstrated sustained release of amoxicillin for up to 8 hours, whereas conventional tablets released 64.77% of the drug within 2 hours. Drug release followed the Higuchi model (R² = 0.989–0.996), indicating diffusion-controlled release. These findings demonstrate that breadfruit peel-derived pectin is a promising natural polymer for gastroretentive floating bead formulations and exhibits performance comparable to commercial pectin.